Optimization of Microsoft Kaizala as an Interactive Media for Cybercounseling During the Covid-19 Pandemic - Sudirman, M Yunus; Haliq, Muh Idham; Putri, Suci Nora Julina; Hidayah, Karisma Khoirul (Universitas Muhammadiyah Metro, 2023)
Automation technology is essential for maximizing counseling services provided by counselors, particularly during the covid-19 pandemic. Cybercounseling requires the use of interactive media technology so that counseling services for students can continue to function optimally. Microsoft Kaizala is used for the interactive media planned to optimize cyber counseling during the COVID-19 pandemic because it is easier to use and has more unique features than other programs. This research uses library research (Library Research) to collect and analyze research-related literature sources from books, proceedings articles, and journals.